Strategy maps : converting intangible assets into tangible outcomes - Kaplan, Robert S. (Harvard Business School Press, 2004)
"Robert S. Kaplan and David P. Norton introduced a revolutionary performance measurement system called the Balanced Scorecard to enable companies to quantify critical intangibles such as people, information, and culture." "Based on their work with more than 300 organizations spanning over a dozen years, Kaplan and Norton have created a new tool that has turned out to be as important an innovation as the Balanced Scorecard itself: strategy maps.